2022
DOI: 10.3389/fchem.2022.852988
|View full text |Cite
|
Sign up to set email alerts
|

Glycopolymer-Wrapped Carbon Nanotubes Show Distinct Interaction of Carbohydrates With Lectins

Abstract: Glyconanomaterials with unique nanoscale property and carbohydrate functionality show vast potential in biological and biomedical applications. We investigated the interactions of noncovalent complexes of single-wall carbon nanotubes that are wrapped by disaccharide lactose-containing glycopolymers with the specific carbohydrate-binding proteins. The terminal galactose (Gal) of glycopolymers binds to the specific lectin as expected. Interestingly, an increased aggregation of nanotubes was also observed when in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…These include spherical scaffolds (e.g., inorganic nanoparticles, fullerenes, dendrimers, hyperbranched polymers, polymersomes, etc. ), tubular/rod-shaped structures (e.g., gold nanorods, carbon nanotubes, and cylindrical micelles), ,, planar sheets (e.g., graphene nanosheets), , and structures that are less well-defined (e.g., linear polymers) , or more complex in shape. ,, Since these results are obtained with scaffolds of different glycan composition, softness, size, shape, and glycan density, it is difficult to directly compare results from one another to draw general conclusions. While studies have shown that the scaffold size and shape can affect their lectin binding and pathogen inhibition properties, ,, ,,, the molecular mechanisms underlying such differences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These include spherical scaffolds (e.g., inorganic nanoparticles, fullerenes, dendrimers, hyperbranched polymers, polymersomes, etc. ), tubular/rod-shaped structures (e.g., gold nanorods, carbon nanotubes, and cylindrical micelles), ,, planar sheets (e.g., graphene nanosheets), , and structures that are less well-defined (e.g., linear polymers) , or more complex in shape. ,, Since these results are obtained with scaffolds of different glycan composition, softness, size, shape, and glycan density, it is difficult to directly compare results from one another to draw general conclusions. While studies have shown that the scaffold size and shape can affect their lectin binding and pathogen inhibition properties, ,, ,,, the molecular mechanisms underlying such differences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…inorganic nanoparticles, fullerenes, dendrimers, hyper-branched polymers, polymersomes, etc), [16][17][18][19][20][21][22][23][24][25][26] tubular structures (e.g. carbon nanotubes, cylindrical micelles), [27][28][29] planar sheets (e.g. graphene nanosheets), 29,30 as well as structures that are less well-defined (e.g.…”
Section: ■ Introductionmentioning
confidence: 99%